Maternal glucose intolerance reduces offspring nephron endowment and increases glomerular volume in adult offspring - Hokke, Stacey; Gretz, Norbert (Diabetes, metabolism research and reviews, 2016)
Background Animal studies report a nephron deficit in offspring exposed to maternal diabetes, yet are limited to models of severe hyperglycaemia which do not reflect the typical clinical condition and which are associated with foetal growth restriction that may confound nephron endowment. We aimed to assess renal morphology and function in offspring of leptin receptor deficient mice (Leprdb/+) and hypothesized that exposure to impaired maternal glucose tolerance (IGT) would be detrimental to the developing kidney. Methods Nephron endowment was assessed in offspring of C57BKS/J Leprdb/+ and +/+ mice at embryonic day (E)18 and postnatal day (PN)21 using design-based stereology. Transcutaneous measurement of renal function and total glomerular volume were assessed in 6-month-old offspring. Only +/+ offspring of Leprdb/+ dams were analysed. Results Compared with +/+ dams, Leprdb/+ dams had a 20% and 35% decrease in glucose tolerance prior to pregnancy and at E17.5 respectively. Offspring of IGT Leprdb/+ dams had approximately 15% fewer nephrons at E18.5 and PN21 than offspring of +/+ dams. There was no difference in offspring bodyweight. Despite normal renal function, total glomerular volume was 13% greater in 6-month-old offspring of IGT Leprdb/+ dams than in +/+ offspring. Conclusions IGT throughout gestation resulted in a nephron deficit that was established early in renal development. Maternal IGT was associated with glomerular hypertrophy in adult offspring, likely a compensatory response to maintain normal renal function. Given the increasing prevalence of IGT, monitoring glucose from early in gestation may be important to prevent altered kidney morphology. Copyright © 2016 John Wiley & Sons, Ltd.